PENGEMBANGAN LKS PRAKTIKUM PADA POKOK BAHASAN LAJU REAKSI UNTUK KELAS XI SMA/MA MELALUI PENERAPAN GREEN CHEMISTRY (DI SMAN 31 JAKARTA) - Ade Irma Hifzhiah; Suwirman Nuryadin; Darsef Darwis (Jurnal Riset Pendidikan Kimia (JRPK), 2013)
This research has intended to develop Student Work Sheet for lab activities in XI senior high school of reaction rate subject by green chemistry applied. This research was done on February until June 2012 at JHS 31 Jakarta and Chemistry Department, Mathematics and Natural Science Faculty, Universitas Negeri Jakarta. This research used by Research and Development (R n D) method with qualitative description approach. The method consists by three parts, there are: Preliminary Study is (literature study and observed) Next, Development Phase has for evaluated and revised about trial product w Last, Experiment Phase is for knowing judgment’s student about product . Based on the final testing, it has a conclusion that Student Work Sheet has acceptable for guiding students in lab activities by contained a few of aspects , there are: content, language, presented, and green chemistry concept. Keywords: Student Work Sheet, Lab Activities, Green Chemistry, R n D method